2002
DOI: 10.1385/bter:90:1-3:99
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Chromium Chloride Supplementation on Performance, Some Serum Parameters, and Immune Response in Broilers

Abstract: This study was conducted to investigate the effect of increasing dietary levels of inorganic chromium (CrCl3 x 6H2O) on the performance, blood chemistry, and immune response of broilers. Eighty newly hatched Ross PM3 broiler chicks were evenly distributed to five groups of 16 chicks each. Two groups (control and only sheep red blood cell inoculated) were fed the basal diet containing 2.2 and 4.5 mg Cr/kg and the remaining groups were fed 20, 40, or 80 mg/kg Cr-supplemented diets for 44 d. Chicks in all groups,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
37
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 29 publications
8
37
2
1
Order By: Relevance
“…Sahin et al [6] found that diets supplemented with CrPic (400 mg Cr/kg diet) resulted in a decrease in serum TC concentrations in stressful conditions. Contrary, under the normal rearing conditions, Uyanik et al [32] found that CrCl 3 added in different concentrations (20,40, 80 mg Cr/kg diet) did not affect serum TC. Motozono et al [24] reported that TC and TG in the serum showed no change associated with the addition of CrPic to the diet under normal rearing conditions.…”
Section: Discussionmentioning
confidence: 93%
“…Sahin et al [6] found that diets supplemented with CrPic (400 mg Cr/kg diet) resulted in a decrease in serum TC concentrations in stressful conditions. Contrary, under the normal rearing conditions, Uyanik et al [32] found that CrCl 3 added in different concentrations (20,40, 80 mg Cr/kg diet) did not affect serum TC. Motozono et al [24] reported that TC and TG in the serum showed no change associated with the addition of CrPic to the diet under normal rearing conditions.…”
Section: Discussionmentioning
confidence: 93%
“…Lien et al (2001) também avaliaram a suplementação de cromo na dieta frangos de corte (1.600 e 3.200 μg /kg) e verificaram diminuição dos níveis de glicose, VLDL e LDL e aumento de triglicérides e HDL. Uyanik et al (2002) suplementaram a dieta de poedeiras com 20 ppm de cromo e não notaram redução significativa dos níveis sorológicos de colesterol total, apesar da queda nos níveis de triglicérides. Por outro lado, Sands & Smith (2002) utilizaram picolinato de cromo e manganês proteinado na dieta de frangos de corte e não observaram variação nas concentrações sorológicas de ácidos graxos não-esterificados, triglicérides, HDL e colesterol total, porém os níveis de ácidos graxos não-esterificados tenderam a uma diminuição.…”
Section: Resultsunclassified
“…Several studies demonstrated that Cr dietary incorporation results in improved the immune response and immune functions of broilers (Bahrami et al, 2012).Enhancement of the cellmediated immune responses in chickens (Rajalekshmi et al, 2014). Improved the proliferation of peripheral blood lymphocytes in birds (Uyanik et al, 2002) .Higher antibody titers against Newcastle disease and infectious bronchitis viruses (Ebrahimzadeh et al, 2012). Enhanced the vaccination response against Newcastle disease and Influenza viruses in broiler chickens (Naghieh et al, 2010) .…”
Section: Discussionmentioning
confidence: 99%